Study on improving antioxydant and antibacterial activities of silk fibroin by irradiation treatment - Tran , Bang Diep; Nguyen , Van Binh; Hoang , Phuong Thao; Hoang , Dang Sang; Nguyen Thuy , Huong Trang (Nuclear Science and Technology, 2014)
The silk fibroin solutions were prepared in solvent system of CaCl2. CH3CH2OH. H2O (mole ratio = 1:2:8) followed dialysis against deionized water. The 3% silk fibroin solutions were irradiated under gamma Co-60 source with dose ranging from 0 to 50 kGy at Hanoi Irradiation Centre and bio-activities of the irradiated silk fibroin solutions were investigated with different radiation doses. The results indicated that the antioxidant and antibacterial activities of fibroin were much improved by gamma irradiation. Maximum value of DPPH radical scavenging activity was 70.4% for the solution of silk fibroin irradiated at 10 kGy. Silk fibroin solutions irradiated at doses higher than 10 kGy also exhibited rather high antibacterial activity against E. coli and S. aureus. In order to estimate the applicability of our irradiated fibroin, the silk fibroin solutions were lyophilized to obtain a pure fibroin powder, then their bio-activities were compared with those of commercial silk fibroin (Proteines De Soie/ Zijdeproteine, Bioflore, Canada). Our fibroin powder revealed higher antioxidant and antibacterial activities. The amino acid compositions of our irradiated fibroin were also higher than that of the commercial product. Thus, the irradiated silk fibroin can be used for further application in cosmetic and other related fields.